Design and Development of a Stamping Press Capable of Punching Microscale Holes in Polymer Membranes. - Schmitt, Eric. (2017)
Abstract: A hand operated benchtop stamping press was developed to conduct research on microscale hole fabrication in polymer membranes for applications as scaffolds in tissue engineering. Die clearances of less than 3 μm were achieved with direct microscope alignment. Female dies were fabricated by laser cutting stainless steel while male dies were produced by either using 200 μm gage pins or deep reactive ion etching of silicon wafers. Polycaprolactone membranes between 30 μm and 45 μm thick were fabricated by hot melt extrusion. The problem of excessive strain to yield, which caused the punched out material to remain attached to the workpiece, was overcome by cooling the membrane and die sets with liquid nitrogen to take advantage of induced brittle behavior below the polymer's glass transition temperature. While cooled, 200 μm holes were successfully punched in 33 μm thick polycaprolactone membranes with 11% die clearance, achieving 73% porosity.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Thomas James.; Committee: Robert White, and Lisa Freed.; Keyword: Mechanical engineering.